Psychosomatic treatment for allergic diseases - Yoshihara, Kazufumi (Biopsychosoc Med, 2015)
Many reports have been published concerning how psychosocial stress influences the occurrence and progression of allergic diseases such as bronchial asthma and atopic dermatitis. As for asthma, a typical allergic disease often accompanied by psychosomatic related problems, the Global Initiative for Asthma (GINA), international medical guidelines for asthma, describes psychosocial problems as causative factors of poor asthma control and as risk factors for asthma exacerbation, even if symptoms are well controlled. However, because there is little high quality evidence for effective treatments for asthma patients with psychosocial problems, concrete assessments and treatments for such problems is scarcely described in GINA. Therefore, psychosomatic intervention for asthma patients is not effectively conducted on a worldwide scale. In contrast, the “Japanese Guidelines for the Diagnosis and Treatment of Psychosomatic Diseases” describe the assessment and treatment of psychosomatic disorders in detail. In the guidelines, psychosocial factors are classified into five categories; 1) Relation between stress and asthma occurrence or progression, 2) Relation between emotion and asthma symptoms, 3) Problems related to a patient’s character and behaviors, 4) Problems of daily life and Quality of Life (QOL), and 5) Problems related to family relationships and life history. The employment of a self-administered questionnaire, the “Psychosomatic Questionnaire related to Asthmatic Occurrence and Progression”, is useful for clarifying psychosocial factors and for setting up treatment strategies according to the problems identified. The Japanese guidelines have been proven to be useful, but empirical evidence for their effectiveness is still relatively limited. It will be necessary in the future to accumulate high-quality evidence and to revise the psychosomatic approaches in the guidelines that are universally valid.